2004
DOI: 10.1136/hrt.2002.006254
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant tendinous chords with tethering of the tricuspid leaflets: a congenital anomaly causing severe tricuspid regurgitation

Abstract: Objective: To define the entity of tricuspid regurgitation caused by tethering of the tricuspid valve leaflets by aberrant tendinous chords. Design: Retrospective study. Setting: Tertiary care centre (university teaching hospital). Patients: 10 patients with unexplained severe tricuspid regurgitation. Methods: The last 13 500 echocardiographic studies from our facility were reviewed to identify patients with severe unexplained tricuspid regurgitation. Tethering was defined by the presence of aberrant tendinous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…A prominent apical displacement of the septal leaflet of the tricuspid valve from the atrioventricular junction is an intrinsic morphologic feature of Ebstein's anomaly. An indexed offset distance of the tricuspid septal leaflet ⩾8 mm/m 2 has been used or suggested as a diagnostic criterion of Ebstein's anomaly in multiple studies and reviews [10][11][12][13][14][15][16][17] after it was first reported by Shiina et al in 1984, 18 although an overlap of the minimal septal offset distance between the cases with and without Ebstein's anomaly was reported in the same year by other authors. 19 To the best of our knowledge, this criterion has not yet been reviewed comprehensively in neonatal populations.…”
Section: E Bstein's Anomaly Is a Rare Congenital Heartmentioning
confidence: 99%
“…A prominent apical displacement of the septal leaflet of the tricuspid valve from the atrioventricular junction is an intrinsic morphologic feature of Ebstein's anomaly. An indexed offset distance of the tricuspid septal leaflet ⩾8 mm/m 2 has been used or suggested as a diagnostic criterion of Ebstein's anomaly in multiple studies and reviews [10][11][12][13][14][15][16][17] after it was first reported by Shiina et al in 1984, 18 although an overlap of the minimal septal offset distance between the cases with and without Ebstein's anomaly was reported in the same year by other authors. 19 To the best of our knowledge, this criterion has not yet been reviewed comprehensively in neonatal populations.…”
Section: E Bstein's Anomaly Is a Rare Congenital Heartmentioning
confidence: 99%
“…The chest radiograph shows right atrial and right ventricular enlargement and normal pulmonary vascularity. 1,11,17,[29][30][31][32][33][34][35][36][37][38][39][40] An electrocardiograph usually shows right axis deviation, right atrial enlargement, right bundle branch block, and first degree atrioventricular block, 1,27,29 and sometimes prolonged corrected QT interval. 29 There may be sinus tachycardia, supraventricular extrasystoles, and atrial fibrillation.…”
Section: Investigationsmentioning
confidence: 99%
“…29 There may be sinus tachycardia, supraventricular extrasystoles, and atrial fibrillation. 11,17,[29][30][31][32][33][34][35][36][37][38][39][40] Cardiac catheterisation reveals elevated right atrial pressure, a pronounced ''V'' wave of tricuspid regurgitation, normal right ventricular pressure, and sometimes a right-to-left shunt at the atrial level. 1,[10][11][12][13][14][15][33][34][35][36][37][38] However, cardiac catheterisation is not required to make a diagnosis in the present day.…”
Section: Investigationsmentioning
confidence: 99%
“…A few cases have been reported, where artificial chords were inserted because of leaflet tethering due to short chordae or a total absence of chordae [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%